Clinical and genetic analysis of epilepsy with myoclonic-atonic seizures caused by SLC6A1 gene variant - Li, Zhen; Han, Changming; Zhao, Hongwei (Frontiers in Pediatrics, 2025)
ObjectiveThis research intends to examine the clinical characteristics and genetic diversity of a child experiencing epilepsy with myoclonic-atonic seizures (EMAS) attributed to a variant in the SLC6A1 gene.MethodsA male child diagnosed with EMAS underwent clinical and electroencephalographic evaluation. Peripheral blood samples were collected for DNA extraction and subsequent whole-exon gene sequencing. For previously identified patients, high-throughput sequencing was utilized, whereas Sanger sequencing was employed for the parents to determine the site of the gene mutation and examine the connection between genotype and phenotype.ResultsThe male child showed delays in intellectual and language development before the disease began. At 1 year and 2 months, he had a febrile seizures, which was succeeded by seizures at 2 years and 9 months; these seizures presented as generalized tonic-clonic, myoclonic, and myoclonic-atonic seizures, along with symptoms showing inattention and hyperactivity. After receiving treatment with levetiracetam (50 mg·kg·d−1), the child has been free of seizures for the last 8 months. Genetic analysis indicated a heterozygous missense variant of c.263T > C (p.L88P) in the SLC6A1 gene in the child, recognized as a spontaneous mutation that has not been previously documented in the literature.ConclusionThe variant in the SLC6A1 gene is implicated as one of the etiological factors contributing to EMAS coupled with neurodevelopmental abnormalities. The identification of this novel mutation enriches the spectrum of known SLC6A1 gene variants.